Use of Selected Scavengers for the Determination of NF-TiO(2) Reactive Oxygen Species during the Degradation of Microcystin-LR under Visible Light Irradiation - PELAEZ, MIGUEL (J Mol Catal A Chem, 2016)
Although UV-induced TiO(2) photocatalysis involves the generation of several reactive oxygen species (ROS), the formation of hydroxyl radicals are generally associated with the degradation of persistent organic contaminants in water. In this study, a variety of radical scavengers were employed to discriminate the roles of different ROS during visible light activated (VLA) photocatalysis using nitrogen and fluorine doped TiO(2) (NF-TiO(2)) in the degradation of the hepatotoxin, microcystin-LR (MC-LR) in water. The addition of hydroxyl radical scavengers, methanol and tert-butyl alcohol to the reaction mixture resulted in negligible inhibition of VLA NF-TiO(2) photocatalytic degradation of MCLR at pH 3.0 and only partial inhibition at pH 5.7. While hydroxyl radicals generally play the primary role in UV TiO(2) photocatalysis, the minimal influence of MeOH and t-BuOH on the degradation process under these experimental conditions indicates hydroxyl radicals ((•)OH) do not play the primary role in VLA NF-TiO(2) photocatalysis. However, strong inhibition was observed in VLA NF-TiO(2) photocatalytic degradation of MC-LR in the presence of superoxide dismutase, benzoquinone and catalase at pH 3.0 and 5.7 indicating O(2)(•−) and H(2)O(2) play critical roles in the degradation process. Similar degradation rates were observed in the presence of singlet oxygen scavenger, deuterium oxide, which enhances singlet oxygen mediated processes further suggesting singlet oxygen does not play a key role in the degradation of MCLR in these system. Formic acid and cupric nitrate were added to probe the roles of the valence band holes and conduction band electrons, respectively. Under UV+vis light irradiation, almost complete inhibition of MC-LR removal is observed with NF-TiO(2) in the presence of (•)OH scavengers at pH 5.7. These results demonstrate that solution pH plays a major role in the formation and reactivities of ROS during VLA NF-TiO(2) photocatalysis. The adsorption strength of the scavengers and MCLR onto NF-TiO(2) as well as the speciation of the ROS as a function of pH need to be carefully considered since they also play a key role in the efficiency of the process. These results indicate the reduction of molecular oxygen by photo-generated electrons rather than hydroxyl radicals produced by oxidative reactions of photo-generated holes play a key role in the of VLA NF-TiO(2) photocatalytic degradation of MC-LR.